High-hardness steel material and its manufacturing method

The development of a high-hardness steel strip with a specific composition and TMCP addresses the challenges of balancing hardness and mechanical properties, achieving enhanced corrosion resistance, impact strength, and formability while reducing manufacturing costs.

JP7654559B2Active Publication Date: 2025-04-01SSAB TECHNOLOGY AB
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021559152
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-11
Filing Date
2020-04-02
Publication Date
2025-04-01
Estimated Expiration
2040-04-02

AI Technical Summary

Technical Problem

Existing high-hardness steel materials face challenges in balancing hardness with impact strength, formability, and resistance to stress corrosion cracking, particularly due to high carbon content which leads to brittleness and increased manufacturing costs.

Method used

A high-hardness steel strip with a specific chemical composition and thermomechanically controlled processing (TMCP) is developed, featuring a microstructure predominantly composed of martensite, which enhances climatic corrosion resistance, impact strength, and formability without the need for tempering.

Benefits of technology

The solution achieves a balance between high hardness and excellent mechanical properties, including improved climatic corrosion resistance, enhanced impact strength, and superior formability, while reducing manufacturing costs by eliminating the tempering step.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654559000005
    Figure 0007654559000005
  • Figure 0007654559000001
    Figure 0007654559000001
  • Figure 0007654559000002
    Figure 0007654559000002
Patent Text Reader

Abstract

Expanding the use of cost-effective thermo-mechanical controlled processing in combination with direct quenching to produce high-hardness steel strip products with improved weather corrosion resistance, guaranteed impact strength and excellent formability / bendability. [Solution] A hot rolled steel strip having the following composition in mass percent: 0.17% to 0.38% C, 0% to 0.5% Si, 0.1% to 0.4% Mn, 0.015% to 0.15% Al, 0.1% to 0.6% Cu, 0.2% to 0.8% Ni, 0.1% to 1% Cr, 0.01% to 0.3% Mo, 0% to 0.005% Nb, 0% to 0.05% Ti, 0% to 0.2% V, 0.0008% to 0.005% B, 0% to 0.025% P, 0.008% or less S, 0.01% or less N, 0% to 0.01% Ca, the balance being Fe and impurities; The steel has a Brinell hardness in the range of 420 to 580 HBW and a corrosion index (ASTM G101-04) of 5 or greater. The above hot rolled steel strip.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high hardness steel strip that exhibits excellent resistance to climatic corrosion and has a good balance between high hardness and excellent mechanical properties such as impact strength, bendability, etc. The present invention also relates to a method for producing the high hardness steel strip. [Background technology]

[0002] High hardness directly affects the wear resistance of steel, and the higher the hardness, the better the wear resistance. High hardness means a Brinell hardness of 450 HBW or more, especially in the range of 500 HBW to 650 HBW.

[0003] Wear resistant steels, also known as impact resistant steels, are used in applications requiring high resistance to wear and impact.

[0004] Such applications can be found in the mining, civil engineering and waste transport industries. Wear resistant steels are used, for example, in the bodies of gravel trucks and in excavator buckets, where the high hardness they offer extends the service life of vehicle components. The benefits of wear resistant steels become even more important when the paint on the exterior surfaces of machines is frequently exposed to mechanical stresses such as impacts, which can cause the paint to become scratched.

[0005] Such high hardness steels are generally obtained by austenitizing steel with a high carbon content (0.41-0.50 wt%) in a furnace, followed by quenching to obtain a martensite structure. In this process, the steel plate is first hot rolled, slowly cooled from the hot rolling temperature to room temperature, reheated to the austenitizing temperature, soaked, and finally quenched to harden.

[0006] Hereinafter, this process is referred to as the RHQ (Reheating and Quenching) process. Examples of steels produced in this way include the wear-resistant steel disclosed in Patent Document 1 and some commercially available wear-resistant steels. Due to the relatively high carbon content required to obtain the desired hardness, the resulting martensitic reaction generates large internal residual stresses in the steel. This is because the higher the carbon content, the greater the lattice distortion. This type of steel is therefore very brittle and may even crack during quenching hardening. To solve this brittleness problem, tempering is usually performed after quenching, which leads to increased processing effort and costs.

[0007] These steels have a high carbon content, which reduces their impact strength, makes them less formable and bendable, and reduces their resistance to stress corrosion cracking (SCC). Stress corrosion cracking is a type of cracking that occurs due to the combined effects of tensile stress and a corrosive environment. Stress corrosion cracking usually begins as pitting corrosion, where the surface of a material appears largely intact, but microscopic cracks that are difficult to detect penetrate the material. Stress corrosion cracking is classified as a catastrophic form of corrosion because these microscopic cracks are very difficult to detect and the damage cannot be easily predicted.

[0008] Therefore, better approaches are needed to reduce the carbon content without compromising hardness and other mechanical properties (such as impact strength, formability / bendability, and resistance to stress corrosion cracking).

[0009] Patent Document 2 and Patent Document 3 relate to RHQ steel sheets having a relatively low carbon content (0.25 to 0.30 wt.% in Patent Document 2, and 0.22 to 0.29 wt.% in Patent Document 3) and a relatively low manganese content. In order to manufacture such RHQ steel sheets, a tempering process is required after quench hardening, which inevitably increases the processing effort and cost.

[0010] Patent Document 4 relates to an abrasion-resistant steel material exhibiting excellent stress corrosion cracking resistance, and this steel plate can be manufactured by a process in which direct quenching (DQ) can be performed immediately after hot rolling without performing a reheating treatment after hot rolling as in the RHQ process. The steel plate of Patent Document 4 is characterized by a relatively low carbon content (0.20 to 0.30 wt.%) and a relatively high manganese content (0.40 to 1.20 wt.%). In order to improve the stress corrosion cracking resistance, it is necessary that the base phase or main phase of the structure of the steel material of Patent Document 4 is tempered martensite.

[0011] On the other hand, the presence of untempered martensite reduces stress corrosion cracking resistance, so the area ratio of untempered martensite is limited to 10% or less.

[0012] From the viewpoint of a balance between wear resistance and stress corrosion cracking resistance, the surface hardness of the steel material in Patent Document 4 is 520 HBW or less.

[0013] The present invention expands the use of cost-effective thermomechanically controlled processing (TMCP) in combination with direct quenching (DQ) to produce high hardness steel strip products that have improved climatic corrosion resistance, guaranteed impact strength and excellent formability / bendability. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] CN102199737 [Patent Document 2] CN102392186 [Patent Document 3] CN103820717 [Patent Document 4] EP2695960 Summary of the Invention [Problem to be solved by the invention]

[0015] In view of the current situation, the object of the present invention is to provide a high hardness steel material with good weather corrosion resistance, reliable impact strength and good formability / bendability. This object is achieved by combining an alloy of specific composition with a cost-effective TMCP process which produces a metallographic structure mainly consisting of martensite. [Means for solving the problem]

[0016] In a first aspect, the present invention provides a hot rolled steel strip comprising the following composition in mass percent (wt.%): C 0.17 to 0.38, preferably 0.21 to 0.35, more preferably 0.22 to 0.28 Si 0 to 0.5, preferably 0.01 to 0.5, more preferably 0.03 to 0.25 Mn 0.1 to 0.4, preferably 0.15 to 0.3 Al 0.015~0.15 Cu 0.1 to 0.6, preferably 0.1 to 0.5, more preferably 0.1 to 0.35 Ni 0 to 0.8, preferably 0.2 to 0.8 Cr is 0.1 to 1, preferably 0.3 to 1, and more preferably 0.35 to 1. More preferably, it is 0.35 to 0.8 Mo: 0.01 to 0.3, preferably 0.03 to 0.3, more preferably 0.05 to 0.3 Nb 0~0.005 Ti 0 to 0.05, preferably 0 to 0.035, more preferably 0 to 0.02 V 0 to 0.2, preferably 0 to 0.06 B 0.0005 to 0.005, preferably 0.0008 to 0.005 P 0 to 0.025, preferably 0.001 to 0.025, more preferably 0.001 to 0.012 S 0 to 0.008, preferably 0 to 0.005 N 0 to 0.01, preferably 0 to 0.005, more preferably 0 to 0.004 Ca 0 to 0.01, preferably 0 to 0.005, more preferably 0.0008 to 0.003 The balance is Fe and impurities.

[0017] Preferably, the composition comprises, in weight percent (wt.%): Ti 0 - 0.005 N 0 - 0.003

[0018] Preferably, the composition comprises, in weight percent (wt.%): Ti>0.005 and ≦0.05 N>0.003 and ≦0.01

[0019] Preferably, [Ni]>[Cu] / 3, more preferably [Ni]>[Cu] / 2, where [Ni] is the amount of Ni in the composition. [Cu] is the amount of Cu in the composition.

[0020] The steel is alloyed with the essential elements Si, Cu, Ni, and Cr, which provides excellent resistance to climatic corrosion and improves the durability of the coating.

[0021] In addition, the Mn content, which is important for improving impact toughness and bending workability, is kept low.

[0022] In order to improve impact toughness and bendability, the Ca / S ratio is adjusted so as not to form CaS, and is preferably in the range of 1 to 2, more preferably 1.1 to 1.7, and further preferably 1.2 to 1.6.

[0023] It is desirable to keep the Nb content as low as possible in order to improve the formability and bendability of steel. Note that elements such as Nb may exist as residuals that are not intentionally added.

[0024] The difference between residuals and impurities is that residuals are alloying elements in controlled amounts and are not considered impurities. Residuals, as typically controlled in industrial processes, do not have a substantial effect on the alloy.

[0025] In a second aspect, the present invention provides a method for producing a hot rolled steel strip, comprising the steps of: - preparing a steel slab according to any one of claims 1 to 5, the steel slab having the chemical composition as stated in the summary; - heating the steel slab to an austenitizing temperature of 1200-1350°C; - hot rolling to the desired thickness at a temperature in the range of Ar3 to 1300 ° C, the finish rolling temperature being in the range of 800 ° C to 960 ° C, preferably in the range of 870 ° C to 930 ° C, more preferably in the range of 885 ° C to 930 ° C; and - direct quenching of the hot rolled strip to a cooling end temperature and coiling temperature of at most 450°C, preferably at most 250°C, more preferably at most 150°C, even more preferably at most 100°C.

[0026] Optionally, the quenched coiled strip is subjected to a tempering step at a temperature in the range of 150° C. to 250° C. However, in the present invention, the tempering step is not required.

[0027] The steel material is a strip steel having a thickness of 10 mm or less, preferably 8 mm or less, more preferably 7 mm or less.

[0028] The resulting steel has a microstructure consisting of at least 90 vol.% martensite, preferably at least 95 vol.% martensite, more preferably at least 98 vol.% martensite, measured from a quarter thickness of the steel. The martensite structure may be untempered, auto-tempered and / or tempered. Preferably, the martensite structure is untempered. More preferably, the microstructure consists of 10 vol.% or more untempered martensite. Preferably, the microstructure consists of 0-1 vol.% retained austenite, more preferably 0-0.5 vol.% retained austenite. Also included are structures such as bainite, ferrite and pearlite.

[0029] The resulting steel has an austenite grain size of 50 μm or less, preferably 30 μm or less, and more preferably 20 μm or less, measured from a quarter thickness of the steel.

[0030] The aspect ratio of the austenite grain structure is one of the factors that affect the impact toughness and bendability of steel.

[0031] To improve impact toughness, it is desirable that the austenite grain structure has an aspect ratio of 1.5 or more, preferably 2 or more, and more preferably 3 or more. To improve bendability, it is desirable that the austenite grain structure has an aspect ratio of 7 or less, preferably 5 or less, and more preferably 1.5 or less.

[0032] The steel material obtained by the present invention has an austenite grain structure with an aspect ratio in the range of 1.5 to 7, preferably 1.5 to 5, and more preferably 2 to 5, and therefore can reliably achieve excellent impact toughness and excellent bending workability in a well-balanced manner.

[0033] The resulting steel has a good balance of hardness and other mechanical properties such as improved weather corrosion resistance, good impact strength, etc. The steel of the present invention has at least one of the following mechanical properties:

[0034] A Brinell hardness in the range of 420 to 580 HBW, preferably 450 to 550 HBW, and more preferably 470 to 530 HBW.

[0035] Corrosion Index (ASTM G101-04) ≧5, preferably ≧5.5, more preferably ≧6.

[0036] 34 J / cm at 20°C or -40°C 2 Above Charpy V impact toughness.

[0037] The steel material of the present invention has excellent bending workability or formability, and has a minimum bending radius of 3.4t or less in a measurement direction in which the bending axis is longitudinal to the rolling direction, and a minimum bending radius of 2.7t or less in a measurement direction in which the bending axis is transverse to the rolling direction, where t is the thickness of the steel strip product.

[0038] The steel material of the present invention has a good balance between high hardness and mechanical properties such as impact strength, formability, and bendability. It also has excellent weather corrosion resistance. [Brief description of the drawings]

[0039] [Figure 1] FIG. 1 is a diagram showing a microstructure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] The term steel is an iron alloy that contains carbon (C).

[0041] Climatic corrosion (also known as atmospheric corrosion) refers to outdoor corrosion caused by local environmental conditions.

[0042] Environmental conditions are shaped by meteorological phenomena such as rain and sun, but also by various impurities in the air, such as chlorides in seawater and sulfur compounds from volcanic activity, industry and mining.

[0043] "Brinell hardness (HBW)" is the designation for the hardness of steel. The Brinell hardness test is performed by pressing a 10 mm spherical tungsten carbide ball with a force of 3000 kilograms against a cleanly prepared surface to produce an imprint, which is then measured to give a numerical value.

[0044] "Corrosion Index (ASTM G101-04)" refers to the American Society for Testing and Materials (ASTM) standard G101, which is the only currently available guide for quantifying the atmospheric corrosion resistance of weather-resistant steels as a function of composition.

[0045] "ACC (Accelerated Continuous Cooling)" refers to the process of accelerating the cooling rate up to a certain temperature and cooling without interruption.

[0046] "UTS (Ultimate Tensile Strength, Rm)" is the limit value at which steel material breaks due to tension, and refers to the maximum tensile stress.

[0047] Yield strength (YS, Rp 0.2 ) refers to the 0.2% offset yield strength, which is defined as the amount of stress that produces 0.2% plastic strain.

[0048] "Total elongation (TEL)" is the percentage of a material that can be stretched before it breaks. It is a rough indicator of formability and is usually expressed as a percentage of a certain gauge length of an extensometer. A typical gauge length is 50 mm (A 50 ) and 80mm(A 80 ).

[0049] "Minimum bend radius (Ri)" refers to the smallest bend radius that can be applied to a test specimen without causing cracks.

[0050] Moreover, "bendability" is the ratio of Ri to the thickness (t) of the sheet.

[0051] The alloy content and processing parameters of the steel determine the microstructure, which in turn determines the mechanical properties of the steel.

[0052] The design of the alloy is the first issue to be considered when developing a steel material with the desired mechanical properties. Next, the chemical composition according to the present invention will be described in more detail. Here, % of each component means % by mass.

[0053] Carbon (C) is used in the range of 0.17% to 0.38%. The inclusion of C increases the strength of the steel material by solid solution strengthening, so the C content determines the strength level. C is used in the range of 0.17% to 0.38% depending on the target hardness. If the carbon content is less than 0.17%, it is difficult to achieve a Brinell hardness of 420 HBW or more. However, C has an adverse effect on weldability, impact toughness, formability or bendability, stress corrosion cracking resistance, etc. Therefore, the C content is set to 0.38% or less. C is preferably used in the range of 0.21% to 0.35%, more preferably 0.22% to 0.28%.

[0054] Silicon Si is used in an amount of less than 0.5%. Si is added to the composition to promote the formation of an oxidation protective layer under conditions of climatic corrosion, imparting good resistance to climatic corrosion and improving the durability of coating layers that are easily damaged or removed from machine surfaces by wear. Si is effective as a deoxidizer and inhibitor to remove oxygen in solution during steelmaking. Alloys of Si increase strength by solid solution strengthening and increase hardness by improving the hardenability of austenite. The presence of Si also stabilizes retained austenite. However, if the Si content exceeds 0.5%, it may unnecessarily increase the carbon equivalent (CE) and reduce weldability. Furthermore, excessive Si may deteriorate the surface quality. As mentioned above, Si is an important element for obtaining sufficient hardness and climatic corrosion resistance and for increasing the durability of the coating film. Preferably, Si is used in the range of 0.01% to 0.5%, more preferably 0.03% to 0.25%.

[0055] Manganese (Mn) is used in the range of 0.1% to 0.4%. Mn lowers the martensite start temperature (Ms) and martensite finish temperature (Mf), and can suppress the autotempering of martensite during quenching. If the autotempering of martensite is suppressed, the internal stress increases, making it more susceptible to cracks and shape distortion due to quenching. A low degree of autotempered martensite structure is advantageous for achieving high hardness, but the adverse effect on impact strength should not be underestimated.

[0056] Mn also increases strength by solid solution strengthening and hardness by increasing the hardenability of austenite. However, if the Mn content is too high, the hardenability of the steel is improved at the expense of impact toughness. Excessive Mn alloying may cause C-Mn segregation and MnS formation, which may induce the formation of initiation sites for pitting corrosion and stress corrosion cracking. Therefore, Mn is used in an amount of 0.1% or more to ensure hardenability, but in an amount of 0.4% or less to avoid the above-mentioned adverse effects and ensure excellent mechanical properties such as impact strength and bendability. Preferably, a low concentration of Mn is used in the range of 0.15% to 0.3%.

[0057] Aluminum Al is used in the range of 0.015% to 0.15%. Al is effective as a deoxidizer or inhibitor that can remove oxygen from the melt during the steelmaking process. Al also removes N by forming stable AlN particles, which refines the grains and is effective for high toughness, especially at low temperatures. Al also stabilizes retained austenite. However, excessive Al can increase nonmetallic inclusions and deteriorate cleanliness.

[0058] Cu is used in the range of 0.1% to 0.6%. Cu is added to the composition to promote the formation of an oxidation protective layer under climatic corrosion conditions, imparting good resistance to climatic corrosion and improving the durability of the coating layer that is easily damaged or removed from the machine surface due to wear. Cu promotes the formation of a low carbon bainite structure, causes solid solution strengthening, and contributes to precipitation strengthening. It is also expected to have the effect of suppressing stress corrosion cracking. If Cu is added in excess, it deteriorates the weldability and the toughness of the heat affected zone (HAZ). Therefore, the upper limit of Cu is set to 0.6%. As mentioned above, Cu is an important element for imparting sufficient hardness and good climatic corrosion resistance and increasing the durability of the coating. Preferably, Cu is used in the range of 0.1% to 0.5%, more preferably 0.1% to 0.35%.

[0059] Nickel Ni is used in an amount up to 0.8%. Ni is used to prevent quench cracking and improve low temperature toughness. Ni is an element that improves the hardenability of austenite and increases strength with little loss of impact toughness or HAZ toughness. Ni also improves surface quality and prevents the occurrence of pitting corrosion, which is the cause of stress corrosion cracking. Ni is added to the composition to promote the formation of an oxidation protective layer under conditions of climatic corrosion. This provides good resistance to climatic corrosion and improves the durability of coating layers that are easily damaged or removed from machine surfaces by abrasion.

[0060] However, nickel contents above 0.8% lead to excessive alloying costs without significant technological improvements. Excessive Ni can produce highly viscous iron oxide scales, degrading the surface quality of steels. High Ni contents also have a negative effect on weldability, as they increase the CE value and the crack susceptibility coefficient. As mentioned above, Ni is an important element to provide sufficient hardness and good weather corrosion resistance without any or little loss of impact toughness, and to increase the durability of coatings. Ni is preferably used in the range of 0.2% to 0.8%.

[0061] Chromium Cr is used in the range of 0.1% to 1%. Cr is added to the composition to promote the formation of an oxidation protective layer under conditions of climatic corrosion. This provides good resistance to climatic corrosion and improves the durability of coating layers that are easily damaged or removed from machine surfaces by wear. The addition of Cr also improves pitting resistance and can prevent the onset of stress corrosion cracking early. As an element that forms medium-strength carbides, Cr improves the strength of both the base metal and the weld, but with only a small decrease in impact toughness. In addition, alloys with Cr improve strength and hardness by increasing the hardenability of austenite.

[0062] However, if the amount of Cr used exceeds 1%, it may have a negative effect on HAZ toughness and on-site weldability. As mentioned above, Cr is an important element for providing sufficient hardness and good weather corrosion resistance without any or no loss of impact toughness, and for enhancing the durability of the coating. Preferably, Cr is used in the range of 0.3% to 1%, more preferably 0.35% to 1%, and even more preferably 0.35% to 0.8%.

[0063] Molybdenum (Mo) is used in the range of 0.01% to 0.3%. Mo improves impact strength, low temperature toughness, and tempering resistance. The presence of Mo increases the hardenability of austenite, thereby improving strength and hardness. Mo can be added to the composition to impart hardenability in place of Mn. In B alloys, Mo is usually required to ensure the effect of B, but Mo is not an economically acceptable alloying element. If Mo is used at more than 0.3%, toughness decreases and the risk of embrittlement increases.

[0064] Furthermore, the inventors have noticed that Mo alloys retard the recrystallization of austenite and increase the aspect ratio of the austenite grain structure. Therefore, the Mo content must be carefully controlled to prevent the austenite grains from being excessively elongated, which deteriorates the bendability of the steel. Preferably, Mo is used in the range of 0.03% to 0.3%, more preferably 0.05% to 0.3%.

[0065] Niobium Nb is used in an amount of up to 0.005%. Nb forms carbides NbC and carbonitrides Nb(C,N). Nb is considered the main grain refining element. Nb contributes to strengthening and toughening of steels. However, excessive Nb deteriorates bendability, especially when direct quenching is performed or when Mo is present in the composition, so the addition of Nb should be limited to 0.005%. In addition, Nb is detrimental to HAZ toughness, since it can promote the formation of coarse upper bainite structure by forming relatively unstable TiNbN or TiNb(C,N) precipitates. To improve the formability and bendability of steel products, the Nb content should be as low as possible.

[0066] Titanium (Ti) is used in an amount of up to 0.05%. TiC precipitates can trap a significant amount of hydrogen H, reducing the diffusivity of H in the material and removing some of the harmful H from the microstructure to prevent stress corrosion cracking. Ti is also added to bind free N, which is harmful to toughness, and form stable TiN, which, together with NbC, can effectively prevent austenite grain growth during the reheating stage at high temperatures.

[0067] The precipitation of TiN also prevents grain coarsening in the HAZ during welding and improves toughness. The formation of TiN inhibits the precipitation of BN, thereby allowing B to contribute to hardenability. For this purpose, the Ti / N ratio is at least 3.4.

[0068] However, if the Ti content is too high, TiN will become coarse and TiC will cause precipitation hardening, which can reduce low-temperature toughness, so the titanium content must be limited to 0.05% or less.

[0069] Preferably, Ti is used in an amount of 0.035% or less, more preferably 0.02% or less. When the nitrogen content of the steel is as low as 0.003% or less, there is no need to add Ti to ensure the boron hardenability effect, and the Ti content can be 0.005% or less. When the nitrogen content is 0.003% or more and 0.01% or less, the Ti content can be 0.005% or more and 0.05% or less.

[0070] Vanadium (V) is used in amounts up to 0.2%. V has essentially the same effect as Nb, but with a smaller effect. 4 C 3 The precipitates of V can trap a significant amount of hydrogen H, reducing the diffusivity of H in the material and removing some of the harmful H from the microstructure, preventing HIC. V is a strong carbide and nitride former, but can also form V(C,N), and its solubility in austenite is higher than that of Nb and Ti. Thus, V alloys have the potential for dispersion strengthening and precipitation strengthening, since a large amount of V can dissolve and precipitate in ferrite. However, the addition of V exceeding 0.2% has a negative effect on weldability and hardenability.

[0071] Preferably, V is used in an amount of 0.06% or less.

[0072] Boron (B) is used in the range of 0.0005% to 0.005%. B is an established element as a microalloy to enhance hardenability. The most effective alloys with B require the presence of Ti, preferably in an amount of at least 3.42N, to prevent the formation of BN. In the presence of nitrogen in an amount of 0.003% or less, the Ti content can be reduced to 0.005% or less, which is favorable for low temperature toughness. If the B content exceeds 0.005%, the hardenability deteriorates.

[0073] Preferably, B is used in the range of 0.0008% to 0.005%.

[0074] Calcium Ca is used in amounts of less than 0.01%. Ca additions in steelmaking are for refining, deoxidation, desulfurization, and to control the shape, size, and distribution of oxide and sulfide inclusions. Ca is usually added to improve subsequent coating. Excessive Ca addition should be avoided to prevent the formation of calcium sulfide (CaS) and / or calcium oxide (CaO), or mixtures of these (CaOS), which would degrade mechanical properties such as bendability and SCC resistance.

[0075] By using Ca in an amount of preferably 0.005% or less, and more preferably 0.0008% to 0.003%, excellent mechanical properties such as impact strength and bendability can be obtained.

[0076] In addition, the impact toughness and bendability can be improved by adjusting the Ca / S ratio so that CaS is not formed. The present inventors have found that, in general, the optimal Ca / S ratio for clean steel materials in steelmaking processes is in the range of 1 to 2, preferably 1.1 to 1.7, and more preferably 1.2 to 1.6.

[0077] The unavoidable impurities include phosphorus (P), sulfur (S), nitrogen (N), etc., and the contents thereof expressed in mass % are preferably defined as follows: P 0 to 0.025, preferably 0.001 to 0.025, more preferably 0.001 to 0.012 S 0 to 0.008, preferably 0 to 0.005, more preferably 0 to 0.002 N 0 to 0.01, preferably 0 to 0.005, more preferably 0 to 0.004

[0078] Other unavoidable impurities include hydrogen H, oxygen O, rare earth metals (REM), etc. Their content is limited to ensure good mechanical properties such as impact toughness.

[0079] The transformation of steels from austenite to martensite is highly dependent on the chemical composition and several processing parameters (mainly reheating temperature, cooling rate and cooling temperature). With regard to the chemical composition, some elements have a greater influence than others, while others have a negligible effect. To evaluate the influence of elements on the formation of martensite during cooling, equations describing the hardenability of austenite can be used. One such equation is shown below:

[0080] From this equation, we can see that the influence of carbon is the largest, the influence of Mn, Mo, and Cr is intermediate, and the influence of Si and Ni is small. Furthermore, this equation indicates that no element is essential for martensite formation, and the absence of one element can be compensated for by the amount of other alloying elements or processing parameters such as cooling rate.

[0081]

number

[0082] Steel products with targeted mechanical properties are manufactured by specific processes which will determine the mechanical properties of the steel product.

[0083] The first step is to provide a steel slab, for example by a process of continuous casting called strand casting.

[0084] In the reheating stage, the steel slab is heated to the austenitizing temperature of 1200-1350°C, followed by a temperature soaking step of 30-150 minutes. This reheating and soaking step is important to control the growth of austenite grains. An increase in the heating temperature can cause dissolution and coarsening of the alloy precipitates, which leads to abnormal grain growth.

[0085] The final steel has a prior austenite grain size measured through one quarter of the strip thickness of 50 μm or less, preferably 30 μm or less, more preferably 20 μm or less.

[0086] In the hot rolling stage, the slab is hot rolled to the desired thickness at a temperature in the range of Ar3-1300°C, and the finish rolling temperature (FRT) is in the range of 800°C-960°C, preferably 870°C-930°C, more preferably 885°C-930°C.

[0087] The aspect ratio of the prior austenite grain structure is one of the factors that affect the impact toughness and bendability of a steel material. In order to improve the impact toughness, the aspect ratio of the prior austenite grain structure is desirably 1.5 or more, preferably 2 or more, and more preferably 3 or more. In order to improve the bendability, the aspect ratio of the prior austenite grain structure is desirably 7 or less, preferably 5 or less, and more preferably 1.5 or less.

[0088] The desired aspect ratio of the austenite grains can be achieved by adjusting a number of parameters, such as the finish rolling temperature, the strain / deformation, the strain rate, and / or alloying with elements such as Mo, which retard the recrystallization of austenite.

[0089] The steel material obtained by the present invention has an austenite grain structure having an aspect ratio in the range of 1.5 to 7, preferably 1.5 to 5, and more preferably 2 to 5, and therefore can reliably achieve excellent impact toughness and excellent bending workability in a well-balanced manner.

[0090] The resulting steel material has a thickness of 10 mm or less, preferably 8 mm or less, and more preferably 7 mm or less.

[0091] The hot-rolled steel strip is directly quenched so that the cooling completion temperature and the coiling temperature are 450° C. or less, preferably 250° C. or less, more preferably 150° C. or less, and further preferably 100° C. or less. The cooling rate is 30° C. / sec or more.

[0092] The directly hardened steel strip is coiled at a temperature of 450°C or less, preferably 250°C or less, more preferably 150°C or less, and even more preferably 100°C or less.

[0093] The resulting steel has a microstructure consisting of at least 90 vol.% martensite, preferably at least 95 vol.% martensite, more preferably at least 98 vol.% martensite, measured from a quarter thickness of the strip. The martensite structure may be untempered, autotempered and / or tempered. Preferably, the martensite structure is untempered. More preferably, the microstructure consists of 10 vol.% or more untempered martensite. Preferably, the microstructure consists of 0-1 vol.% retained austenite, more preferably 0-0.5 vol.% retained austenite. The microstructure may also include bainite, ferrite, pearlite, etc.

[0094] The strip of the present invention provides a balance of hardness and other mechanical properties such as good impact strength, improved weather corrosion resistance, and good formability / bendability.

[0095] The steel strip of the present invention has a high Brinell hardness in the range of 420 to 580 HBW, preferably 450 to 550 HBW, and more preferably 470 to 530 HBW.

[0096] The steel strip has improved resistance to weather-induced corrosion, with a corrosion index (ASTM G101-04) of at least 5, preferably at least 5.5, more preferably at least 6. By using the steel material of the invention, the durability of the coating film is improved and the recoating interval can be increased by 1.5 to 2 times.

[0097] The corrosion index (ASTM G101-04) is used to estimate the long-term atmospheric corrosion of alloy steels in various environments. The formula for the corrosion index (ASTM G101-04) is formed by a statistical method from long-term outdoor corrosion exposure tests, and the formula is expressed as follows: I ASTMG101 =26.01(%Cu)+3.88(%Ni)+1.20(%Cr)+1.49(%Si)+17.28(%P)-7.29(%Cu)(%Ni)-9.10(%Ni)(%P)-33.39(%Cu) 2

[0098] High hardness steel strip has a strength of 34 J / cm at temperatures of -20°C or -40°C. 2 It has a Charpy V impact toughness of or above 100%, and meets the conventional impact strength requirements.

[0099] The steel strip has excellent bending workability or formability. The steel material of the present invention has a minimum bending radius of 3.4t or less in a measurement direction in which the bending axis is longitudinal to the rolling direction, and a minimum bending radius of 2.7t or less in a measurement direction in which the bending axis is transverse to the rolling direction, where t is the thickness of the steel strip. EXAMPLES

[0100] The following examples further describe and demonstrate embodiments of the present invention. The examples are merely illustrative and should not be construed as limiting the invention, since many variations thereof are possible without departing from the scope of the invention.

[0101] The chemical compositions used to manufacture the tested steel strips are given in Table 1. The manufacturing conditions for manufacturing the tested steel strips are given in Table 2. The mechanical properties of the tested steel strips are given in Table 3.

[0102] Microstructure The microstructure can be characterized from SEM micrographs and the volume fraction can be determined using point counting or image analysis methods. All microstructures of tested Examples 1-4 have at least 90 vol.% martensite as the main phase. Figure 1 shows an SEM image of the RD-ND plane from 1 / 4 thickness of strip steel No. 1, where the austenite grain boundaries are visualized. The aspect ratio of the austenite grain boundaries of strip steel No. 1 is 3.4.

[0103] Brinell hardness HBW The Brinell hardness test is carried out by pressing a 10mm spherical tungsten carbide ball with a force of 3000 kilograms on a cleanly prepared surface to make a mark, which is then measured to obtain a specific value. The measurement is performed perpendicular to the top surface of the steel plate, at a depth of 10-15% from the surface of the steel plate. As shown in Table 3, it can be seen that the Brinell harnesses of Examples 1-4 are in the range of 475-491 HBW. Also, Comparative Example 5 shows a Brinell harness of 486 HBW, and Comparative Example 6 shows a Brinell harness of 469 HBW.

[0104] Corrosion Index (ASTM G101-04) The corrosion index (ASTM G101-04) is calculated based on the American Society for Testing and Materials (ASTM) standard G101. As shown in Table 3, the corrosion index (ASTM G101-04) of Examples 1 to 4 was 5.28 or more. On the other hand, the corrosion index (ASTM G101-04) of Comparative Examples Nos. 5 and 6 was significantly low, at 3.4 and 1.04, respectively.

[0105] Charpy V impact toughness The impact toughness values ​​at -20°C or -40°C were determined by a Charpy V-notch test in accordance with the ASME (American Society of Mechanical Engineers) standard. The examples had a Charpy V impact toughness value of 63 J / cm at -20°C. 2 , 45J / cm 2 (Table 3) In addition, in Examples 1 to 4, when the measurement direction was the longitudinal direction of the rolling direction, the Charpy V impact toughness at a temperature of -40°C was 38 to 120 J / cm 2 In addition, in Examples 1 to 4, when the measurement direction is transverse to the rolling direction, the Charpy V impact toughness at a temperature of -40°C is within the range of 58 to 105 J / cm 2 The impact toughness of Examples 1 to 4 is improved compared to Comparative Example 6.

[0106] Comparative Example 5 sacrifices bending workability and has a Charpy V impact toughness value superior to Examples and 2.

[0107] Growth rate Elongation was measured according to ASTM E8 standard using transverse specimens from a batch producing 2000 tonne plate. The average total elongation (A50) values ​​of Examples 1 and 2 were 11.6 and 11.3, respectively (Table 3), better than Comparative Examples 5 and 6, which had average A50 values ​​of 10.1 and 9.1, respectively. Comparative Examples 5 and 6 have better A50 values ​​than Examples 3 and 4, at the expense of Charpy V impact toughness.

[0108] Bending workability The bending test involves plastically deforming the specimen in a three-point bend, in one stroke, until the specified bend angle of 90° is reached after unloading. Inspection and evaluation of the bend is carried out continuously throughout the test series, in order to be able to decide whether the punch radius (R) should be increased, maintained or decreased. The limit of the bending workability of the material (R / t) can be identified in the test series when a minimum defect-free bend length of 3 m is met, with the same punch radius (R) in both the longitudinal and transverse directions. Cracks, surface necking marks and flat bends (significant necking) are registered as defects.

[0109] As a result of the bending test, in all of Examples 1 to 4, the minimum bending radius in the measurement direction perpendicular to the rolling direction was 3.3t or less, and the minimum bending radius in the measurement direction perpendicular to the rolling direction was 2.6t or less, where t is the sheet thickness of the steel strip product (Table 3). In Comparative Example 5, the minimum bending radius in the measurement direction perpendicular to the rolling direction was 3.7t, and the minimum bending radius in the measurement direction transverse to the rolling direction was 2.2t, showing poor bendability.

[0110] yield strength The yield strength was measured according to the ASTM E8 standard using transverse specimens from a 2000 tonne production batch of plate material. For all of Examples 1 to 4, the yield strength (Rp 0.2 ) is in the range of 1302 MPa to 1399 MPa (Table 3). In addition, in Comparative Examples 5 and 6, the yield strength (Rp 0.2 ) are 1262 MPa and 1338 MPa, respectively (Table 3).

[0111] Tensile strength Tensile strength was measured according to the ASTM E8 standard using transverse specimens from a production batch of 2000 ton plates. Each of Examples 1 to 4 has an average ultimate tensile strength (Rm) measured in the longitudinal direction in the range of 1509 MPa to 1566 MPa (Table 3). Comparative Examples 5 and 6 have average ultimate tensile strengths (Rm) measured in the longitudinal direction of 1550 MPa and 1552 MPa, respectively (Table 3).

[0112]

Table 1

[0113]

Table 2

[0114]

Table 3

Claims

1. A hot-rolled steel strip having the following composition, expressed in mass % (wt. %): C 0.17-0.38 Si 0-0.5 Mn 0.1-0.4 Al 0.015~0.15 Cu 0.1 to 0.6 Ni 0 to 0.8 Cr 0.1 to 1 Mo 0.01~0.3 Nb 0 to 0.005 Ti 0 to 0.05 V 0 to 0.2 B 0.0005~0.005 P 0-0.025 S 0 to 0.008 N 0 to 0.01 Ca 0 to 0.01 The balance is Fe and impurities. The steel has a Brinell hardness in the range of 420 to 580 HBW and a corrosion index (ASTM G101-04) of at least 5; When the amount of N is in the range of 0 to 0.003 wt. %, the amount of Ti is in the range of 0 to 0.005 wt. %, having a microstructure consisting of, by volume percent (vol. %), 90% or more martensite, 0-1% retained austenite, and the balance bainite, ferrite and / or pearlite, and having an austenite grain structure with an aspect ratio in the range of 1.5 to 7; The thickness is 10 mm or less. The above hot rolled steel strip.

2. 2. The steel material according to claim 1, wherein the amount of N is 0.003 wt % or more and 0.01 wt % or less, and the amount of Ti is 0.005 wt % or more and 0.05 wt % or less.

3. [Ni]>[Cu] / 3, [Ni] is the amount of Ni in the composition The steel material according to claim 1 or 2, wherein [Cu] is the amount of Cu in the composition.

4. The steel material according to any one of claims 1 to 3, wherein the Ca / S ratio is in the range of 1 to 2.

5. The steel material according to any one of claims 1 to 4, having a Brinell hardness in the range of 450 to 550 HBW.

6. The steel product according to any one of claims 1 to 5, having a corrosion index (ASTM G101-04) of at least 5.

5.

7. The steel material according to any one of claims 1 to 6, having a Charpy V impact toughness of 45 J / cm 2 or more when the temperature in the transverse and / or longitudinal direction is -20°C, and 38 J / cm 2 when the temperature is -40°C.

8. 8. The steel material according to claim 1, characterized in that the bending axis is longitudinal to the rolling direction, the minimum bending radius in the measurement direction parallel to the rolling direction is 3.4t or less, and the bending axis is transverse to the rolling direction, the minimum bending radius in the measurement direction perpendicular to the rolling direction is 2.7t or less, where t is the thickness of the strip steel.

9. The steel material according to any one of claims 1 to 8, wherein the austenite grain size is 50 µm or less.

10. A method for producing a steel material according to any one of claims 1 to 9, comprising the following steps: - providing a steel slab of the chemical composition according to any one of claims 1 to 4; - heating said steel slab to an austenitizing temperature of 1200 to 1350 °C; - hot rolling to the desired thickness at a temperature in the range of Ar3 to 1300 ° C, the finish rolling temperature being in the range of 800 ° C to 960 ° C, - direct quenching of the hot-rolled strip to a cooling temperature below 450°C and to the coiling temperature; - optionally, annealing at a temperature in the range 150°C to 250°C.

Citation Information

Patent Citations

  • 600HB-grade wear resistant steel plate and its manufacturing method

    CN102199737A

  • Manufacturing method of HB500 grade low-manganese wear-resistant steel plate

    CN102392186A

  • Steel plate and preparation method thereof

    CN103820717A

  • Silicon vanadium steel plate with promoted bulletproof performance and manufacturing method

    CN106319347A

  • NM300 wear-resistant steel for high-alumina high-silicon concrete mixer truck and production method of NM300 wear-resistant steel

    CN108411203A